The Influence of Leadership Style on Employee Job Satisfaction in Gorontalo Provincial Government-Indonesia - Ibrahim, Meimoon; lamuda, Ilyas (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aims to analyze how the influence of leadership variables on employee job satisfaction in the regional government of Gorontalo Province. The pattern used is explanatory research, namely the pattern of research that seeks to explain the relationship of variables referred to as formulated in the formulation of hypotheses so that the relationship of variables, namely Leadership Style (X1) and Employee Performance (Y2), can be tested with quantitative approaches and hypothesis testing, used Structural Equation Modeling (SEM) method. The study was conducted in a representative sample, with as many as 200 people from 3,997 employee populations. The results showed that Leadership Style positively and significantly affected job satisfaction in the Provincial Government Gorontalo-Indonesia.